2022
DOI: 10.3389/fpls.2022.967849
|View full text |Cite
|
Sign up to set email alerts
|

Leaf chlorophyll parameters and photosynthetic characteristic variations with stand age in a typical desert species (Haloxylon ammodendron)

Abstract: As a desert shrub, Haloxylon ammodendron combines ecological, economic, and social benefits and plays an important role in the ecological conservation of arid desert areas. Understanding its physiological characteristics and its mechanism of light energy utilization is important for the conservation and utilization of H. ammodendron. Therefore, we selected five stands (5-, 11-, 22-, 34-, and 46-year-old) of H. ammodendron as research objects in the study and measured their photosynthetic light response curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This is influenced by both nutrient conditions and environmental stresses. 53 The total chlorophyll contents of WT plants were found to be significantly lower under PFOS conditions compared to the pht1;8 mutant. This data indicated that the accumulation of PFOS in plants inhibits photosynthesis, thereby impacting overall growth, including a reduction in root length.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is influenced by both nutrient conditions and environmental stresses. 53 The total chlorophyll contents of WT plants were found to be significantly lower under PFOS conditions compared to the pht1;8 mutant. This data indicated that the accumulation of PFOS in plants inhibits photosynthesis, thereby impacting overall growth, including a reduction in root length.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…The quantity of chlorophyll largely determines the photosynthetic capacity of plants, which in turn affects their growth. This is influenced by both nutrient conditions and environmental stresses . The total chlorophyll contents of WT plants were found to be significantly lower under PFOS conditions compared to the pht1;8 mutant.…”
Section: Resultsmentioning
confidence: 96%
“…It is worth noting that proteins translated from edited RNAs could play a critical function in an environment change context, resulting in plant acclimatization and survival capabilities [ 49 ]. Indeed, H. ammodendron is well known for its remarkable tolerance to saline and dry environments [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…After long-term natural selection, they have shown strong adaptability to habitats, so they are important for wind control and sand control in the Gurbantunggut Desert ( Yue et al., 2020 ). Extensive research has been conducted on H. ammodendron and H. persicum , mainly focusing on the effects of environmental change (such as topographic change, precipitation change, and nitrogen addition) on their community structure, growth, development, physiological performance, and water use pattern ( Xu and Li, 2006 ; Hao and Li, 2022 ; Song et al., 2010 ; Wu et al., 2019b ; He et al., 2022 ; Qiang et al., 2022 ). However, little research has been conducted on the links between hydrological conditions and their ecological stoichiometry.…”
Section: Introductionmentioning
confidence: 99%